Conversion of a recA-Mediated Non-toxigenic Vibrio cholerae O1 Strain to a Toxigenic Strain Using Chitin-Induced Transformation - Sinha-Ray, Shrestha; Alam, Meer T.; Bag, Satyabrata; Morris Jr., J. Glenn; Ali, Afsar (Frontiers in Microbiology, 2019)
Toxigenic Vibrio cholerae strains, including strains in serogroups O1 and O139 associated with the clinical disease cholera, are ubiquitous in aquatic reservoirs, including fresh, estuarine and marine environments. Humans acquire cholera by consuming water and/or food contaminated with the microorganism. The genome of toxigenic V. cholerae harbors a cholera-toxin producing prophage (CT-prophage) encoding genes that promote expression of cholera toxin. The CT-prophage in V. cholerae is flanked by two satellite prophages, RS1 and TLC. Using cell surface appendages (TCP and/or MSHA pili), V. cholerae can sequentially acquire TLC, RS1 and CTX phages by transduction; the genome of each of these phages ultimately integrates into V. cholerae’s genome in a site-specific manner. Here, we showed that a non-toxigenic V. cholerae O1 biotype El Tor strain, lacking the entire RS1-CTX-TLC prophage complex (designated as RCT: R for RSI, C for CTX and T for TLC prophage, respectively), was able to acquire RCT from donor genomic DNA (gDNA) of a wild-type V. cholerae strain (E7946) via chitin-induced transformation. Moreover, we demonstrated that a chitin-induced transformant (designated as AAS111) harboring RCT was capable of producing cholera toxin. We also showed that recA, rather than xerC and xerD recombinases, promoted the acquisition of RCT from donor gDNA by the recipient non-toxigenic V. cholerae strain. Our data document the existence of an alternative pathway by which a non-toxigenic V. cholerae O1 strain can transform to a toxigenic strain by using chitin induction. As chitin is an abundant natural carbon source in aquatic reservoirs where V. cholerae is present, chitin-induced transformation may be an important driver in the emergence of new toxigenic V. cholerae strains.